An anatomy of U.S. personal bankruptcy under Chapter 13 - Hülya Eraslan; Gizem Koşar; Wenli Li; Pierre-Daniel Sarte (Federal Reserve Bank of New York, 2016)
We build a structural model of Chapter 13 bankruptcy that captures salient features of personal bankruptcy under Chapter 13. We estimate our model using a novel data set that we construct from bankruptcy court dockets recorded in Delaware in 2001 and 2002. Our estimation results highlight the importance of debtor's choice of repayment plan length for Chapter 13 outcomes under the restrictions imposed by the bankruptcy law. We use the estimated model to conduct policy experiments to evaluate the impact of more stringent provisions of Chapter 13 that impose additional restrictions on the length of repayment plans. We find that these provisions would not materially affect creditor recovery rates and would not necessarily make discharge more likely for debtors with income above the state median.
Keywords: C61; D12; K35; 330; Chapter 13 bankruptcy; discharge; recovery rate